Association of a 13.6-Megadalton Plasmid in Pediococcus pentosaceus with Bacteriocin Activity - Daeschel, Mark A. (1985)
Pediococcus pentosaceus FBB61 and L7230, isolated from cucumber fermentations, produced a bacteriocin, designated pediocin A, which had identical activity spectra against species of Pediococcus, Clostridium, Staphylococcus, and Streptococcus. Both strains possessed a 13.6-megadalton plasmid (pMD136). Plasmid curing experiments suggested that both bacteriocin immunity and production determinants were encoded by pMD136. Use of pediocin-producing strains in food fermentations is discussed.